2022
DOI: 10.1186/s40168-022-01414-9
|View full text |Cite
|
Sign up to set email alerts
|

Taurine metabolism is modulated in Vibrio-infected Penaeus vannamei to shape shrimp antibacterial response and survival

Abstract: Background Numerous microorganisms are found in aquaculture ponds, including several pathogenic bacteria. Infection of cultured animals by these pathogens results in diseases and metabolic dysregulation. However, changes in the metabolic profiles that occur at different infection stages in the same ponds and how these metabolic changes can be modulated by exogenous metabolites in Penaeus vannamei remain unknown. Results Here, we collected gastroint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 107 publications
1
8
0
Order By: Relevance
“…PCR analyses were conducted for the following pathogens in animal samples: hepanhamaparvovirus (DHPV) [ 16 ]; Macrobrachium bidnavirus (MrBdv) [ 17 ]; decapod iridescent virus 1 (DIV1) [ 18 ]; white spot syndrome virus (WSSV) [ 19 ]; infectious hypodermal and haematopoietic necrosis virus (IHHNV) [ 20 , 21 , 22 , 23 ]; Wenzhou shrimp virus 8 (WzSV8) [ 24 ]; P. vannamei nodavirus [ 25 ]; covert mortality nodavirus (CMNV) [ 26 ]; infectious myonecrosis virus (IMNV) [ 27 ]; yellow head virus (YHV) [ 28 ]; gill-associated virus (GAV) [ 28 ]; Taura syndrome virus (TSV) [ 29 , 30 ]; Macrobrachium nodavirus (MrNV) [ 31 ]; extra small virus (XSV) usually associated with MrNV [ 32 ]; Spiroplasma [ 33 ]; Vibrio spp. ( Vibrio -specific 16S rRNA gene fragment) [ 34 ]; V. parahaemolyticus (collagenase gen) [ 35 ]; V. parahaemolyticus (gen vhvp-1and gen vhvp-2) [ 36 ]; V. parahaemolyticus (gen tdh) [ 37 ]; V. harveyi (gen vhh) [ 37 ]; Rickettsia -like bacteria (RLB) [ 38 ]; necrotizing hepatopancreatitis bacteria (NHP-B) [ 39 ]; Ecytonucleospora ( Enterocytozoon ) hepatopenaei (EHP) [ 40 ]; non-EHP Microsporidia [ 41 ]; acute hepatopancreatic necrosis disease (AHPND) [ 42 ]; and Haplosporidia [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PCR analyses were conducted for the following pathogens in animal samples: hepanhamaparvovirus (DHPV) [ 16 ]; Macrobrachium bidnavirus (MrBdv) [ 17 ]; decapod iridescent virus 1 (DIV1) [ 18 ]; white spot syndrome virus (WSSV) [ 19 ]; infectious hypodermal and haematopoietic necrosis virus (IHHNV) [ 20 , 21 , 22 , 23 ]; Wenzhou shrimp virus 8 (WzSV8) [ 24 ]; P. vannamei nodavirus [ 25 ]; covert mortality nodavirus (CMNV) [ 26 ]; infectious myonecrosis virus (IMNV) [ 27 ]; yellow head virus (YHV) [ 28 ]; gill-associated virus (GAV) [ 28 ]; Taura syndrome virus (TSV) [ 29 , 30 ]; Macrobrachium nodavirus (MrNV) [ 31 ]; extra small virus (XSV) usually associated with MrNV [ 32 ]; Spiroplasma [ 33 ]; Vibrio spp. ( Vibrio -specific 16S rRNA gene fragment) [ 34 ]; V. parahaemolyticus (collagenase gen) [ 35 ]; V. parahaemolyticus (gen vhvp-1and gen vhvp-2) [ 36 ]; V. parahaemolyticus (gen tdh) [ 37 ]; V. harveyi (gen vhh) [ 37 ]; Rickettsia -like bacteria (RLB) [ 38 ]; necrotizing hepatopancreatitis bacteria (NHP-B) [ 39 ]; Ecytonucleospora ( Enterocytozoon ) hepatopenaei (EHP) [ 40 ]; non-EHP Microsporidia [ 41 ]; acute hepatopancreatic necrosis disease (AHPND) [ 42 ]; and Haplosporidia [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the following pathogens were screened for from isolated bacteria: Vibrio spp. ( Vibrio -specific 16S rRNA gene fragment) [ 34 ]; V. parahaemolyticus (collagenase gen) [ 35 ]; V. parahaemolyticus (gen vhvp-1and gen vhvp-2) [ 36 ]; V. parahaemolyticus (gen tdh) [ 37 ]; V. harveyi (gen vhh) [ 37 ]; and toxR gen [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…To identify bacterial ( V. parahaemolyticus (AHPND) ) abundance in the hemolymph samples, RT-qPCR-based methods were used. First, a standard curve was prepared using V. parahaemolyticus (AHPND) strains and gene-specific primers (PirB, Table 1 ) as previously described ( 27 ). Next, RT-qPCR assay was performed using primers specific to the V. parahaemolyticus (AHPND) strain (PirB, Table 1 ) and the DNA extracted above.…”
Section: Methodsmentioning
confidence: 99%
“…Plant proteins are generally deficient in taurine, possibly explaining part of their lower attractiveness and palatability [34]. In addition to increased feed intake, supplementation of taurine in diets for juvenile whiteleg shrimp has been found to improve growth performance, metabolism, immunity, anti-oxidant capacity, and intestinal health [35][36][37][38][39]. Metabolomic fingerprinting of C. finmarchicus has also revealed that one of its major metabolites is betaine [40], which is a highly soluble glycine derivative with chemoattractive properties for both fish and shrimp [8][9][10][41][42][43].…”
Section: Feed Intake and Ch/km Inclusion Ratesmentioning
confidence: 99%